Method for preparing fertilizer by extracting minerals from threonine fermentation waste liquid

By using graphene nanosheets modified carbon nanotube materials in the treatment of threonine fermentation waste liquid, catalyzed the oxidation and decomposition of threonine threonine, and using modified diatomaceous earth and functionalized cellulose to extract minerals, the problems of waste resources and insufficient stability of liquid fertilizers in the prior art are solved, and the effect of efficient utilization of waste liquid resources and preparation of high-quality liquid fertilizers is achieved.

CN119661269AInactive Publication Date: 2025-03-21NINGXIA TAISHENG BIOTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411922171.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art cannot fully utilize threonine and minerals when treating threonine fermentation waste liquid, resulting in waste of resources and environmental pollution, and the stability and nutritional richness of the prepared liquid fertilizer are insufficient.

Method used

By collecting the threonine fermentation waste liquid for pretreatment and decomposition, the carbon nanotube material modified with graphene nanosheets is used as a composite catalyst to catalyze the hydrogen peroxide to produce strong oxidative hydroxyl radicals, oxidize and decompose threonine, and use a composite composed of modified diatomaceous earth and functional cellulose to efficiently extract minerals, and finally prepare a stable and nutritious liquid fertilizer.

Benefits of technology

The utilization efficiency of threonine fermentation waste liquid is improved, environmental pollution is reduced, and the stability and nutritional content of prepared liquid fertilizers are significantly improved, meeting the efficient needs of agricultural production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661269A_ABST
    Figure CN119661269A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a fertilizer by extracting mineral substances from threonine fermentation waste liquid, and relates to the technical field of fertilizer preparation, the method has the advantages that a graphene nanosheet modified carbon nanotube material is selected as a basis of a composite catalyst, the surface and the periphery of a carbon nanotube are wrapped with graphene nanosheets, and the composite catalyst is prepared; a large number of wrinkles and pore structures are formed, the specific surface area of the material is greatly increased, the material is put into an acid solution to be soaked and pretreated, surface functional groups are activated, manganese dioxide oxide nanoparticles are better loaded, and in the threonine decomposition process, the specific surface area of the material is greatly increased. The transition metal oxide nanoparticles efficiently catalyze hydrogen peroxide to generate hydroxyl radicals with strong oxidizing property, and the hydroxyl radicals and threonine are quickly subjected to oxidation reaction to decompose the threonine into substances such as carbon dioxide, water and small-molecular organic acid, so that good conditions are created for subsequent mineral extraction and liquid fertilizer preparation; the utilization efficiency of the threonine fermentation waste liquid is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fertilizer preparation, in particular to a method for preparing fertilizer by extracting minerals from threonine fermentation waste liquid. Background Art

[0002] With the continuous development of biotechnology, threonine, as an important amino acid, has been widely used in the fields of medicine, food and feed. The production of threonine is mainly carried out through fermentation process. However, a large amount of waste liquid is generated in the threonine fermentation process. These waste liquids not only contain unused threonine, but also contain rich nutrients such as minerals. If they are not properly treated, the threonine fermentation waste liquid will not only cause serious pollution to the environment, but also waste the precious resources in it. The prior art has certain technical defects. First, when treating threonine in threonine fermentation waste liquid, the prior art cannot fully utilize the threonine in the fermentation waste liquid to prepare fertilizer, resulting in a waste of resources. Secondly, the prior art is not efficient enough in extracting minerals from the waste liquid, and it is difficult to efficiently extract minerals for the preparation of liquid fertilizer. Furthermore, the liquid fertilizer prepared by the prior art may lack stability and nutritional richness, and cannot meet the high-efficiency needs of agricultural production. To this end, we propose a method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer. Summary of the invention

[0003] The object of the present invention is to provide a method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer.

[0004] In order to solve the problems raised in the above background technology, the present invention provides the following technical solution: a method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer, the method for preparing fertilizer specifically comprises the following steps: Step 1: Collect threonine fermentation waste liquid and pre-treat it, let the threonine fermentation waste liquid stand for a period of time by gravity sedimentation, let larger particles of impurities naturally settle to the bottom, then use a filter to filter, remove unsettled large particles of impurities and suspended matter, then add flocculant polyaluminium chloride, stir evenly and let it stand again for a period of time, let small particles of impurities condense into larger particles and then filter and remove, completing the preliminary filtration and purification of the waste liquid; Step 2, decomposing threonine, firstly preparing a composite catalyst material, selecting a carbon nanotube material modified by graphene nanosheets, pre-treating it with dilute hydrochloric acid, so that the material forms a uniformly dispersed morphological structure with a high specific surface area and abundant pores, then subjecting it to a high-temperature carbonization treatment, obtaining a porous carbon skeleton with a high specific surface area and abundant pore structure, and then immersing it in a manganese sulfate solution by an impregnation method, so that the manganese salt is decomposed into manganese dioxide oxide nanoparticles and loaded on the porous carbon skeleton to obtain a composite catalyst material, and the prepared composite catalyst material is put into the pre-treated waste liquid, and a hydrogen peroxide solution with a concentration of 20 is added for oxidation reaction, and the transition metal oxide nanoparticles catalyze the hydrogen peroxide to produce a strongly oxidizing hydroxyl radical, which undergoes an oxidation reaction with the remaining threonine in the waste liquid, and decomposes the threonine into carbon dioxide, water and small molecular organic acid substances; Step 3: Filter the mixed solution after threonine decomposition by vacuum filtration to separate the composite catalyst material, and then further process the filtrate, first adjust the pH value of the filtrate, and then add sodium carbonate precipitant to the filtrate for precipitation for a period of time to precipitate the mineral ions in the filtrate, then filter and collect the precipitate, and collect the obtained precipitate after washing and drying, as an important raw material for preparing liquid fertilizer; Step 4, preparing a composite material consisting of modified diatomaceous earth and functionalized cellulose, first modifying the diatomaceous earth, first grinding the diatomaceous earth, then soaking it in a hydrochloric acid solution for a period of time, washing and drying it, and then soaking it in a solution containing a metal ion chelating agent for a period of time to obtain modified diatomaceous earth, then functionalizing the natural cellulose, soaking the natural cellulose material cotton fiber in a sodium hydroxide solution for a period of time to react, washing it with deionized water after the reaction is completed, adding an initiator ammonium persulfate to an acrylic acid solution containing a grafting monomer after washing to obtain functionalized cellulose, mixing the modified diatomaceous earth and the functionalized cellulose to obtain a composite material, filtering the waste liquid again and then putting it into the composite material for reaction, filtering and separating the composite material after the reaction, and then soaking the composite material in a dilute hydrochloric acid solution for a period of time. During this process, the dilute hydrochloric acid reacts with the minerals in the composite material to elute the adsorbed minerals to obtain a mineral-rich solution; Step 5: Take the product after the decomposition of threonine in step 2 and the mineral-rich solution obtained in step 4, mix them evenly to obtain a mineral solution, dissolve the organic polymer polyacrylamide in water, and then add the mineral solution to the organic polymer solution for reaction. Then, add the plant growth regulator indoleacetic acid, potassium dihydrogen phosphate buffer and stabilizer disodium ethylenediaminetetraacetate to the mixed solution, then adjust the pH value of the solution and stir evenly to obtain liquid fertilizer.

[0005] As a further solution of the present invention: in the step 1, the standing time of the threonine fermentation waste liquid is 30 minutes, the filtration pore size of the filter is 0.5mm-1.2mm, the amount of flocculant polyaluminium chloride added is 0.5%-1% of the volume of the waste liquid, and after adding, it is stirred evenly and allowed to stand again for 1 hour.

[0006] As a further solution of the present invention: in the step 2, the pretreatment process of the carbon nanotube material modified with graphene nanosheets is as follows: the carbon nanotube material modified with graphene nanosheets is soaked in dilute hydrochloric acid for 2h-3h, then washed with deionized water until neutral, and then dried at 80℃-100℃ for 4h-6h. After the pretreatment, it is subjected to high-temperature carbonization treatment. The high-temperature carbonization treatment process is as follows: in the presence of inert gas nitrogen, the temperature is raised to 6 at a heating rate of 5℃ / min-10℃ / min. 00℃-800℃, the high temperature carbonization treatment time is 3h-5h, and then the activation treatment is carried out at 700℃-900℃ with activating agent carbon dioxide for 2h-4h, and then it is immersed in manganese sulfate solution by impregnation method. The impregnation process is as follows: the porous carbon skeleton is immersed in a manganese sulfate solution with a concentration of 0.5mol / L-1mol / L for 4h-6h, and then dried at 80℃-120℃ for 6h-8h, and then calcined at 300℃-400℃ for 2h-3h.

[0007] As a further solution of the present invention: in the step 2, the composite catalyst material is put into the pretreated waste liquid and then a hydrogen peroxide solution is added to carry out an oxidation reaction, the concentration of the hydrogen peroxide solution is 10%-20%, the amount of the hydrogen peroxide solution added is 5%-10% of the volume of the waste liquid, and the reaction is carried out for 2.5h-4.5h at a temperature of 45°C-55°C and a stirring speed of 120r / min-180r / min.

[0008] As a further scheme of the present invention: in the step three, the mixed solution after the decomposition of threonine is filtered by vacuum filtration with a filter membrane pore size of 0.1mm-0.3mm and a vacuum degree of -0.05MPa to -0.08MPa. The filtrate is then treated by first adjusting the pH value to 6.5-7.5, and then adding sodium carbonate precipitant for a precipitation time of 2h-4h.

[0009] As a further scheme of the present invention: in the step 4, the diatomite modification process is as follows: first grind the diatomite to a particle size of 0.1mm-0.5mm, soak it in a hydrochloric acid solution with a concentration of 0.5mol / L-1mol / L for 2h-3h, dry it at 100℃-120℃ for 3h-4h after washing, and then soak it in a metal ion chelating agent solution with a concentration of 0.2mol / L-0.5mol / L, and react it at 40℃-50℃ for 3h-4h. The natural cellulose functionalization treatment process is as follows: soak the natural cellulose material cotton fiber under alkaline conditions of 1mol / L-2mol / L sodium hydroxide solution for 2h-3h, add the initiator ammonium persulfate to the acrylic acid solution containing the grafting monomer after washing, and react it at 50℃-60℃ for 3h-4h to obtain functionalized cellulose.

[0010] As a further scheme of the present invention: in the step 4, the modified diatomaceous earth and the functionalized cellulose are mixed in a mixing ratio of 1:1.5-2 by mass ratio of the modified diatomaceous earth to the functionalized cellulose, the waste liquid is reacted with the composite material again at 25°C-35°C for 2h-3h, the concentration of the dilute hydrochloric acid solution for soaking the composite material is 0.5mol / L-1mol / L, and the soaking time is 2h-3h.

[0011] As a further solution of the present invention: in the step five, the organic polymer polyacrylamide is dissolved in water, specifically, 10mL-15m water is added per gram of polyacrylamide to form a solution with a concentration of 5%-10%, the mass ratio of the polyacrylamide solution and the mineral solution added to the organic solution is 1:3-4, and the reaction is controlled to stir and mix at 40°C-50°C for 2h-3h.

[0012] As a further scheme of the present invention: in the step 5, the concentration of the plant growth regulator indoleacetic acid added to the mixed solution is 0.01mol / L-0.03mol / L, potassium dihydrogen phosphate buffer is added until its concentration in the solution is 0.1mol / L-0.3mol / L, the amount of the stabilizer disodium ethylenediaminetetraacetate added is 0.5%-1% of the mass of the solution, and then the pH value of the solution is adjusted to 7-7.5, and finally stirred at a stirring speed of 60r / min-100r / min for 30min-60min to obtain liquid fertilizer.

[0013] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are: 1. The present invention selects a carbon nanotube material modified by graphene nanosheets as the basis of the composite catalyst, wherein the graphene nanosheets have a two-dimensional planar structure; the carbon nanotubes have a tubular structure. When the two are combined, the carbon nanotubes serve as a supporting skeleton, and the graphene nanosheets are tightly wrapped on the surface and around the carbon nanotubes, forming a large number of wrinkles and pore structures together, thereby greatly improving the specific surface area of ​​the material. The material is pre-treated by soaking in an acid solution to activate the surface functional groups, so that a strong chemical bond and physical adsorption effect can be formed between the material and the manganese dioxide oxide nanoparticles, thereby better loading the manganese dioxide oxide nanoparticles. In the decomposition process of threonine, the transition metal oxide nanoparticles efficiently catalyze hydrogen peroxide to produce strongly oxidizing hydroxyl radicals, and the hydroxyl radicals quickly react with threonine to decompose it into harmless carbon dioxide, water, small molecular organic acids and other substances. This process greatly improves the removal efficiency of threonine, creates good conditions for the subsequent extraction of minerals and the preparation of liquid fertilizers, greatly improves the utilization efficiency of threonine fermentation waste liquid, and reduces environmental pollution, thereby achieving effective utilization of resources. 2. The present invention prepares a composite material composed of modified diatomite and functionalized cellulose. After the modified diatomite is ground, it is soaked in a hydrochloric acid solution, washed and dried, and then soaked in a solution containing a metal ion chelating agent to react, so that chelating groups are loaded on its surface. These chelating groups can form stable complexes with mineral ions in the waste liquid, thereby achieving adsorption of minerals. The modified diatomite strongly adsorbs the minerals in the waste liquid by combining chelation and physical adsorption. The functionalized cellulose soaks the natural cellulose material under alkaline conditions, washes it, and then adds an initiator to a solution containing a specific grafting monomer to react, so that functional groups with adsorption properties such as carboxyl and hydroxyl are grafted on the cellulose surface. These functional groups can react chemically with mineral ions to form chemical bonds, thereby achieving chemical adsorption. The functionalized cellulose further enhances the adsorption capacity of minerals through this chemical adsorption. After the two are mixed, they work synergistically to efficiently extract the minerals in the waste liquid, provide rich nutrients for the preparation of liquid fertilizers, and achieve effective recovery and reuse of resources. 3. The present invention prepares a composite material composed of an organic polymer and inorganic mineral particles. An organic polymer such as polyacrylamide is dissolved in water to form a solution of a specific concentration, which provides a good medium for combining with the inorganic mineral particles. An appropriate amount of water is added to the polyacrylamide to ensure the concentration and fluidity of the solution so as to fully interact with the inorganic mineral particles. The inorganic mineral particles are obtained by further processing the minerals in step four, and react to form a stable composite material. At the same time, trace elements and plant growth regulators are added to provide rich nutrients for the liquid fertilizer. Potassium dihydrogen phosphate buffer and stabilizer disodium ethylenediaminetetraacetate are added to adjust the pH value and ionic strength of the solution so that it is in a state suitable for preparing liquid fertilizer, so that the prepared liquid fertilizer has stable performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A schematic diagram of the method steps in an embodiment of the present invention; Figure 2 It is a schematic diagram for comparing the performance of the embodiment and the comparative example in the embodiment of the present invention. DETAILED DESCRIPTION

[0015] The specific embodiments of the present invention will be further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.

[0016] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0017] Please see attached Figure 1 -Attached Figure 2 The present invention provides a method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer, and the method for preparing fertilizer specifically comprises the following steps: Step 1: Collect threonine fermentation waste liquid and pre-treat it, let the threonine fermentation waste liquid stand for a period of time by gravity sedimentation, let larger particles of impurities naturally settle to the bottom, then use a filter to filter, remove unsettled large particles of impurities and suspended matter, then add flocculant polyaluminium chloride, stir evenly and let it stand again for a period of time, let small particles of impurities condense into larger particles and then filter and remove, completing the preliminary filtration and purification of the waste liquid; Step 2, decomposing threonine, firstly preparing a composite catalyst material, selecting a carbon nanotube material modified by graphene nanosheets, pre-treating it with dilute hydrochloric acid, so that the material forms a uniformly dispersed morphological structure with a high specific surface area and abundant pores, then subjecting it to a high-temperature carbonization treatment, obtaining a porous carbon skeleton with a high specific surface area and abundant pore structure, and then immersing it in a manganese sulfate solution by an impregnation method, so that the manganese salt is decomposed into manganese dioxide oxide nanoparticles and loaded on the porous carbon skeleton to obtain a composite catalyst material, and the prepared composite catalyst material is put into the pre-treated waste liquid, and a hydrogen peroxide solution with a concentration of 20 is added for oxidation reaction, and the transition metal oxide nanoparticles catalyze the hydrogen peroxide to produce a strongly oxidizing hydroxyl radical, which undergoes an oxidation reaction with the remaining threonine in the waste liquid, and decomposes the threonine into carbon dioxide, water and small molecular organic acid substances; Step 3: Filter the mixed solution after threonine decomposition by vacuum filtration to separate the composite catalyst material, and then further process the filtrate, first adjust the pH value of the filtrate, and then add sodium carbonate precipitant to the filtrate for precipitation for a period of time to precipitate the mineral ions in the filtrate, then filter and collect the precipitate, and collect the obtained precipitate after washing and drying, as an important raw material for preparing liquid fertilizer; Step 4, preparing a composite material consisting of modified diatomaceous earth and functionalized cellulose, first modifying the diatomaceous earth, first grinding the diatomaceous earth, then soaking it in a hydrochloric acid solution for a period of time, washing and drying it, and then soaking it in a solution containing a metal ion chelating agent for a period of time to obtain modified diatomaceous earth, then functionalizing the natural cellulose, soaking the natural cellulose material cotton fiber in a sodium hydroxide solution for a period of time to react, washing it with deionized water after the reaction is completed, adding an initiator ammonium persulfate to an acrylic acid solution containing a grafting monomer after washing to obtain functionalized cellulose, mixing the modified diatomaceous earth and the functionalized cellulose to obtain a composite material, filtering the waste liquid again and then putting it into the composite material for reaction, filtering and separating the composite material after the reaction, and then soaking the composite material in a dilute hydrochloric acid solution for a period of time. During this process, the dilute hydrochloric acid reacts with the minerals in the composite material to elute the adsorbed minerals to obtain a mineral-rich solution; Step 5: Take the product after the decomposition of threonine in step 2 and the mineral-rich solution obtained in step 4, mix them evenly to obtain a mineral solution, dissolve the organic polymer polyacrylamide in water, and then add the mineral solution to the organic polymer solution for reaction. Then, add the plant growth regulator indoleacetic acid, potassium dihydrogen phosphate buffer and stabilizer disodium ethylenediaminetetraacetate to the mixed solution, then adjust the pH value of the solution and stir evenly to obtain liquid fertilizer.

[0018] In one embodiment of the present invention: in step 1, the standing time of the threonine fermentation waste liquid is 30 minutes, the filtration pore size of the filter is 0.5mm-1.2mm, the amount of flocculant polyaluminium chloride added is 0.5%-1% of the volume of the waste liquid, and after adding, it is stirred evenly and allowed to stand again for 1 hour.

[0019] In one embodiment of the present invention, in step 2, the pretreatment process of the graphene nanosheet-modified carbon nanotube material is as follows: the graphene nanosheet-modified carbon nanotube material is soaked in dilute hydrochloric acid for 2h-3h, then washed with deionized water until neutral, and then dried at 80℃-100℃ for 4h-6h. After the pretreatment, it is subjected to high-temperature carbonization treatment. The high-temperature carbonization treatment process is as follows: surrounded by inert gas nitrogen, the temperature is raised to 6 at a heating rate of 5℃ / min-10℃ / min. 00℃-800℃, the high temperature carbonization treatment time is 3h-5h, and then the activation treatment is carried out at 700℃-900℃ with activating agent carbon dioxide for 2h-4h, and then it is immersed in manganese sulfate solution by impregnation method. The impregnation process is as follows: the porous carbon skeleton is immersed in a manganese sulfate solution with a concentration of 0.5mol / L-1mol / L for 4h-6h, and then dried at 80℃-120℃ for 6h-8h, and then calcined at 300℃-400℃ for 2h-3h.

[0020] In one embodiment of the present invention: in step 2, the composite catalyst material is put into the pretreated waste liquid and then a hydrogen peroxide solution is added for oxidation reaction, the concentration of the hydrogen peroxide solution is 10%-20%, the amount of hydrogen peroxide solution added is 5%-10% of the volume of the waste liquid, and the reaction is carried out for 2.5h-4.5h at a temperature of 45°C-55°C and a stirring speed of 120r / min-180r / min.

[0021] In one embodiment of the present invention: in step three, the mixed solution after threonine decomposition is filtered by vacuum filtration with a filter membrane pore size of 0.1mm-0.3mm, and a vacuum degree of -0.05MPa to -0.08MPa. The filtrate is then treated by first adjusting the pH value to 6.5-7.5, and then adding sodium carbonate precipitant for a precipitation time of 2h-4h.

[0022] In one embodiment of the present invention: in step four, the diatomite modification process is as follows: first grind the diatomite to a particle size of 0.1mm-0.5mm, soak it in a hydrochloric acid solution with a concentration of 0.5mol / L-1mol / L for 2h-3h, dry it at 100℃-120℃ for 3h-4h after washing, and then soak it in a metal ion chelating agent solution with a concentration of 0.2mol / L-0.5mol / L, and react it at 40℃-50℃ for 3h-4h. The natural cellulose functionalization treatment process is as follows: soak the natural cellulose material cotton fiber under alkaline conditions of 1mol / L-2mol / L sodium hydroxide solution for 2h-3h, add the initiator ammonium persulfate to the acrylic acid solution containing the grafting monomer after washing, and react it at 50℃-60℃ for 3h-4h to obtain functionalized cellulose.

[0023] In one embodiment of the present invention: in step 4, the modified diatomaceous earth and the functionalized cellulose are mixed in a mixing ratio of 1:1.5-2 by mass ratio of the modified diatomaceous earth to the functionalized cellulose, the waste liquid is reacted with the composite material again at 25°C-35°C for 2h-3h, the concentration of the dilute hydrochloric acid solution for soaking the composite material is 0.5mol / L-1mol / L, and the soaking time is 2h-3h.

[0024] In one embodiment of the present invention: in step five, the organic polymer polyacrylamide is dissolved in water, specifically, 10mL-15m water is added per gram of polyacrylamide to form a solution with a concentration of 5%-10%, the mass ratio of the polyacrylamide solution and the mineral solution added to the organic solution is 1:3-4, and the reaction is controlled to stir and mix at 40°C-50°C for 2h-3h.

[0025] In one embodiment of the present invention: in step 5, the concentration of indoleacetic acid, a plant growth regulator, added to the mixed solution is 0.01 mol / L-0.03 mol / L, potassium dihydrogen phosphate buffer is added until its concentration in the solution is 0.1 mol / L-0.3 mol / L, the amount of disodium ethylenediaminetetraacetate, a stabilizer, added is 0.5%-1% of the mass of the solution, and then the pH value of the solution is adjusted to 7-7.5, and finally stirred at a stirring speed of 60r / min-100r / min for 30min-60min to obtain liquid fertilizer.

[0026] In one embodiment of the present invention: in step 2, the porous carbon skeleton after high-temperature carbonization is subjected to surface plasma treatment to enhance its binding force with manganese dioxide oxide nanoparticles, the treatment time is 1h-2h, the treatment power is 500W-800W, and the surface plasma treatment can introduce specific active sites on the surface of the material, further improving the binding stability between the porous carbon skeleton and the manganese dioxide oxide nanoparticles, thereby enhancing the catalytic effect of the composite catalyst in the process of oxidizing threonine; In one embodiment of the present invention: in step 3, a specific ion complexing agent is added to the filtrate after vacuum filtration, and the ion complexing agent acts synergistically with the precipitant to improve the precipitation efficiency of mineral ions. The amount of the ion complexing agent added is 0.2%-0.5% of the mass of the filtrate, and the complexing reaction time is 1h-2h. By adding the ion complexing agent, a more stable complex can be formed with the mineral ions in the filtrate, and the ion complexing agent acts together with the sodium carbonate precipitant to significantly improve the precipitation speed and precipitation amount of the mineral ions, providing a richer source of minerals for the liquid fertilizer; In one embodiment of the present invention: in step 4, the functionalized cellulose is subjected to a secondary grafting treatment, and organic molecules with specific adsorption properties are grafted onto the surface of the functionalized cellulose. The grafting reaction is carried out at 60° C.-70° C., the reaction time is 2 h-3 h, and the concentration of the grafting agent is 0.1 mol / L-0.3 mol / L. The secondary grafting treatment can further increase the adsorption properties of the functionalized cellulose, so that after forming a composite material with modified diatomaceous earth, the functionalized cellulose can more efficiently adsorb minerals in the waste liquid, thereby improving the extraction efficiency of minerals and the nutrient content of the liquid fertilizer. In one embodiment of the present invention: in step 5, in the process of preparing liquid fertilizer, a specific microbial agent is added to promote the absorption and utilization of nutrients in the fertilizer by plants. The amount of the microbial agent added is 0.1%-0.3% of the solution mass, and the mixture is added to the mixed solution after being cultured and activated at 30°C-40°C for 1h-2h. The addition of the microbial agent can improve the soil microecological environment, enhance the absorption and utilization efficiency of the nutrients in the liquid fertilizer by the plant roots, and improve the use effect of the fertilizer; Example 1, please refer to the attached Figure 1 -Attached Figure 2First, the threonine fermentation waste liquid was collected for pretreatment, and the waste liquid was allowed to settle by gravity for 30 minutes to allow larger particles of impurities to settle naturally. Then, it was filtered with a filter with a pore size of 1.2 mm to remove unsettled large particles of impurities and suspended matter. Then, polyaluminum chloride, a flocculant accounting for 1% of the volume of the waste liquid, was added, stirred evenly and allowed to stand for another hour to allow small particles of impurities to condense into larger particles and then filtered and removed. Then, threonine was decomposed, and the carbon nanotube material modified with graphene nanosheets was selected, soaked in dilute hydrochloric acid for 3 hours, washed with deionized water until neutral, and then dried at 100°C for 6 hours. In a nitrogen atmosphere, the temperature was increased to 800°C at a heating rate of 10°C / min for high-temperature carbonization treatment for 5 hours, and then carbon dioxide was used at 900°C. The obtained porous carbon skeleton was activated for 4 hours, and then immersed in a 1 mol / L manganese sulfate solution for 6 hours, dried at 120°C for 8 hours, and then calcined at 400°C for 3 hours to obtain a composite catalyst material, which was put into the pretreated waste liquid, and a hydrogen peroxide solution with a concentration of 20% and a volume of 10% of the waste liquid was added, and the reaction was carried out at 55°C and a stirring speed of 180r / min for 4.5 hours to decompose threonine into carbon dioxide, water and small molecular organic acid substances. After that, the mixed solution after the decomposition of threonine was filtered by vacuum filtration, the pore size of the filter membrane was 0.3mm, the vacuum degree was -0.08MPa, the composite catalyst material was separated, and the pH value of the filtrate was adjusted to 7 .5, add sodium carbonate precipitant to precipitate for 4 hours, precipitate the mineral ions in the filtrate, filter and collect the precipitate, wash and dry it, and then prepare the composite material, first grind the diatomaceous earth to a particle size of 0.5mm, soak it in 1mol / L hydrochloric acid solution for 3 hours, dry it at 120℃ for 4 hours after washing, and then soak it in 0.5mol / L metal ion chelating agent solution, react it at 50℃ for 4 hours to obtain modified diatomaceous earth, soak the cotton fiber in 2mol / L sodium hydroxide solution for 3 hours, add initiator ammonium persulfate to the acrylic acid solution containing the grafted monomer after washing, and react it at 60℃ for 4 hours to obtain functionalized cellulose, the two are mixed in a mass ratio of 1:2, and the waste liquid is then After the first filtration, the composite material was added, reacted at 35°C for 3 hours, and then filtered to separate the composite material. The composite material was then immersed in a 1 mol / L dilute hydrochloric acid solution for 3 hours to obtain a solution rich in minerals. Finally, the product after the decomposition of threonine and the solution rich in minerals were taken to prepare a composite material composed of an organic polymer and inorganic mineral particles. The organic polymer polyacrylamide was dissolved in water, and 15 ml of water was added to each gram of polyacrylamide to form a solution with a concentration of 10%. The mineral solution was added to the organic polymer solution at a mass ratio of 1:4, and the mixture was stirred and mixed at 50°C for 3 hours. Then, a plant growth regulator indoleacetic acid with a concentration of 0.03 mol / L and a plant growth regulator indoleacetic acid with a concentration of 0.3 mol / L potassium dihydrogen phosphate buffer and 1% of the solution mass of the stabilizer disodium ethylenediaminetetraacetate, adjust the pH value of the solution to 7.5, and finally stir at a stirring speed of 100 r / min for 60 minutes to obtain liquid fertilizer.

[0027] Comparative Example 1, please refer to the attached Figure 1 -Attached Figure 2First, the threonine fermentation waste liquid was collected and decomposed, and the carbon nanotube material modified with graphene nanosheets was selected and immersed in dilute hydrochloric acid for 2 hours. After being washed with deionized water until neutral, it was dried at 80°C for 4 hours, and heated to 600°C at a heating rate of 5°C / min in a nitrogen atmosphere for high-temperature carbonization treatment for 3 hours, and then activated with carbon dioxide at 700°C for 2 hours. The obtained porous carbon skeleton was then immersed in a 0.5 mol / L manganese sulfate solution for 4 hours, dried at 80°C for 6 hours, and then calcined at 300°C for 2 hours to obtain a composite catalyst material, which was put into the threonine fermentation waste liquid, and peroxide with a concentration of 10% and a volume of 5% of the waste liquid was added. Hydrogen solution, react for 2.5 hours at 45°C and a stirring speed of 120r / min to decompose threonine into carbon dioxide, water and small molecular organic acid substances. After that, the mixed solution after the decomposition of threonine is filtered by vacuum filtration, the pore size of the filter membrane is 0.1mm, the vacuum degree is -0.05MPa, and the composite catalyst material is separated. The pH value of the filtrate is adjusted to 6.5, and sodium carbonate precipitant is added for precipitation for 2 hours to precipitate the mineral ions in the filtrate. The precipitate is collected by filtration, washed, dried and collected, and then a composite material is prepared. The diatomaceous earth is first ground to a particle size of 0.1mm, soaked in a 0.5mol / L hydrochloric acid solution for 2 hours, and then washed and The fiber was dried at 100°C for 3 hours, then immersed in a 0.2 mol / L metal ion chelating agent solution, reacted at 40°C for 3 hours to obtain modified diatomaceous earth, the cotton fiber was immersed in a 1 mol / L sodium hydroxide solution for 2 hours, and after washing, an initiator ammonium persulfate was added to an acrylic acid solution containing a grafting monomer, and reacted at 50°C for 3 hours to obtain functionalized cellulose, the two were mixed at a mass ratio of 1:1.5, the waste liquid was filtered again and then put into the composite material, reacted at 25°C for 2 hours, and then filtered to separate the composite material, and then the composite material was immersed in a 0.5 mol / L dilute hydrochloric acid solution for 2 hours to obtain a mineral-rich solution, and finally, the product after the decomposition of threonine and the rich A composite material composed of an organic polymer and inorganic mineral particles is prepared by dissolving the organic polymer polyacrylamide in water, adding 10 ml of water to each gram of polyacrylamide to form a solution with a concentration of 5%, adding the mineral solution to the organic polymer solution in a mass ratio of 1:3, stirring and mixing at 40°C for 2 hours, then adding 0.01 mol / L of indoleacetic acid, a plant growth regulator, 0.1 mol / L of potassium dihydrogen phosphate buffer and 0.5% of the solution mass of a stabilizer disodium ethylenediaminetetraacetate to the mixed solution, adjusting the pH value of the solution to 7, and finally stirring at a stirring speed of 60 r / min for 30 minutes to obtain a liquid fertilizer.

[0028] Comparative Example 2, please refer to the attached Figure 1 -Attached Figure 2First, the threonine fermentation waste liquid was collected for pretreatment, and the waste liquid was allowed to settle by gravity for 30 minutes to allow larger particles of impurities to settle naturally. Then, a filter with a pore size of 1.2 mm was used to filter out the unsettled large particles of impurities and suspended matter. Then, polyaluminum chloride, a flocculant accounting for 1.5% of the volume of the waste liquid, was added, stirred evenly, and allowed to stand for another hour to allow small particles of impurities to condense into larger particles and then filtered out. Then, threonine was decomposed, and the carbon nanotube material modified with graphene nanosheets was selected, soaked in dilute hydrochloric acid for 3 hours, washed with deionized water until neutral, and then dried at 100°C for 6 hours. In a nitrogen atmosphere, the temperature was raised to 900°C at a heating rate of 20°C / min for high-temperature carbonization treatment for 5 hours, and then carbon dioxide was used for 100 The obtained porous carbon skeleton was activated at 0°C for 4 hours, and then immersed in a 1 mol / L manganese sulfate solution for 6 hours, dried at 120°C for 8 hours, and then calcined at 400°C for 3 hours to obtain a composite catalyst material, which was put into the pretreated waste liquid, and a hydrogen peroxide solution with a concentration of 5% and a volume of 10% of the waste liquid was added, and reacted at 55°C and a stirring speed of 180r / min for 4.5 hours to decompose threonine into carbon dioxide, water and small molecular organic acid substances. After that, the mixed solution after the decomposition of threonine was filtered by vacuum filtration, the pore size of the filter membrane was 0.3mm, the vacuum degree was -0.08MPa, the composite catalyst material was separated, and the pH value of the filtrate was adjusted to 7.5, adding sodium carbonate precipitant for precipitation for 4 hours, precipitating the mineral ions in the filtrate, filtering and collecting the precipitate, washing and drying, and then preparing the composite material, first grinding the diatomaceous earth to a particle size of 0.5 mm, soaking it in a 2 mol / L hydrochloric acid solution for 3 hours, washing it and drying it at 120°C for 4 hours, then soaking it in a 0.3 mol / L metal ion chelating agent solution, reacting it at 50°C for 4 hours to obtain modified diatomaceous earth, soaking the cotton fiber in a 3 mol / L sodium hydroxide solution for 3 hours, washing it, adding initiator ammonium persulfate to an acrylic acid solution containing a grafted monomer, reacting it at 60°C for 4 hours to obtain functionalized cellulose, and mixing the two in a mass ratio of 1:2, and then removing the waste liquid. After the first filtration, the composite material was added, reacted at 35°C for 3 hours, and then filtered to separate the composite material. The composite material was then immersed in a 1 mol / L dilute hydrochloric acid solution for 3 hours to obtain a solution rich in minerals. Finally, the product after the decomposition of threonine and the solution rich in minerals were taken to prepare a composite material composed of an organic polymer and inorganic mineral particles. The organic polymer polyacrylamide was dissolved in water, and 15 ml of water was added to each gram of polyacrylamide to form a solution with a concentration of 10%. The mineral solution was added to the organic polymer solution at a mass ratio of 1:4, and the mixture was stirred and mixed at 50°C for 3 hours. Then, a plant growth regulator indoleacetic acid with a concentration of 0.03 mol / L and a plant growth regulator indoleacetic acid with a concentration of 0.3 mol / L potassium dihydrogen phosphate buffer and 1% of the solution mass of the stabilizer disodium ethylenediaminetetraacetate, adjust the pH value of the solution to 7.5, and finally stir at a stirring speed of 100 r / min for 60 minutes to obtain liquid fertilizer.

[0029] Comparative Example 3: First, threonine fermentation waste liquid was collected for pretreatment, and the waste liquid was allowed to settle by gravity for 30 minutes to allow larger particles of impurities to settle naturally, and then filtered with a filter with a pore size of 1.2 mm to remove unsettled large particles of impurities and suspended matter, and then polyaluminum chloride, a flocculant accounting for 1% of the volume of the waste liquid, was added, stirred evenly and allowed to stand again for 1 hour to allow small particles of impurities to condense into larger particles and then filtered and removed, and then threonine was decomposed, and activated carbon-loaded titanium dioxide material was selected, immersed in dilute sulfuric acid for 3 hours, washed with deionized water to neutrality, and then dried at 100°C for 6 hours, heated to 800°C at a heating rate of 10°C / min in a nitrogen atmosphere for high-temperature carbonization treatment for 5 hours, and then activated with carbon dioxide at 900°C for 4 hours, and then The obtained porous carbon skeleton was then immersed in a 1 mol / L copper sulfate solution for 6 hours, dried at 120°C for 8 hours, and then calcined at 400°C for 3 hours to obtain a composite catalyst material, which was put into the pretreated waste liquid, and a hydrogen peroxide solution with a concentration of 20% and a volume of 10% of the waste liquid was added, and the reaction was carried out at 55°C and a stirring speed of 180r / min for 4.5 hours to decompose threonine into carbon dioxide, water and small molecular organic acid substances. After that, the mixed solution after the decomposition of threonine was filtered by vacuum filtration, the pore size of the filter membrane was 0.3mm, the vacuum degree was -0.08MPa, and the composite catalyst material was separated. The pH value of the filtrate was adjusted to 7.5, and sodium carbonate precipitant was added for precipitation for 4 hours. The mineral ions in the liquid are precipitated, and the precipitate is collected by filtering. After washing and drying, the precipitate is collected and then prepared into a composite material. The zeolite is first ground into a particle size of 0.5 mm, and then immersed in a 1 mol / L nitric acid solution for 3 hours. After washing, it is dried at 120°C for 4 hours, and then immersed in a 0.5 mol / L metal ion chelating agent solution. The modified zeolite is reacted at 50°C for 4 hours to obtain the modified zeolite. The wood fiber is immersed in a 2 mol / L potassium hydroxide solution for 3 hours. After washing, an initiator potassium persulfate is added to an acrylic acid solution containing a grafted monomer, and the reaction is carried out at 60°C for 4 hours to obtain functionalized wood fiber. The two are mixed in a mass ratio of 1:2, and the waste liquid is filtered again and then put into the composite material, reacted at 35°C for 3 hours, and then filtered to separate the composite material. Then, the composite material was immersed in a 1 mol / L dilute hydrochloric acid solution for 3 hours to obtain a solution rich in minerals. Finally, the product after the decomposition of threonine and the solution rich in minerals were taken to prepare a composite material composed of organic polymers and inorganic mineral particles. The organic polymer polyvinyl alcohol was dissolved in water, and 15 m of water was added to each gram of polyvinyl alcohol to form a solution with a concentration of 10%. The mineral solution was added to the organic polymer solution at a mass ratio of 1:4. The mixture was stirred and mixed at 50°C for 3 hours. Then, 0.03 mol / L of naphthaleneacetic acid, a plant growth regulator, 0.3 mol / L of potassium dihydrogen phosphate buffer, and 1% of the solution mass of trisodium citrate, a stabilizer, were added to the mixed solution to adjust the pH value of the solution to 7.5. Finally, stir at a stirring speed of 100r / min for 60 minutes to obtain liquid fertilizer.

[0030] Designing the Experiment Experimental material preparation: the same batch of threonine fermentation waste liquid, graphene nanosheet modified carbon nanotube material, dilute hydrochloric acid, deionized water, flocculant polyaluminium chloride, hydrogen peroxide solution, sodium carbonate precipitant, diatomaceous earth, hydrochloric acid solution, solution containing metal ion chelating agent, cotton fiber, sodium hydroxide solution, acrylic acid solution containing grafting monomer, initiator ammonium persulfate, dilute hydrochloric acid solution, organic polymer polyacrylamide, plant growth regulator indoleacetic acid, potassium dihydrogen phosphate buffer, stabilizer disodium ethylenediaminetetraacetate, activated carbon loaded titanium dioxide material, zeolite, nitric acid solution, wood fiber, initiator potassium persulfate, organic polymer polyvinyl alcohol, plant growth regulator naphthylacetic acid and stabilizer trisodium citrate; Experimental equipment: electronic balance, atomic absorption spectrometer, high performance liquid chromatograph, spectrophotometer and measuring cylinder; Experimental steps: According to the methods of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3, threonine fermentation waste liquid was treated respectively, three groups were set for each, and the experimental data were averaged; For each experimental sample, record the following data: Composite catalyst material separation efficiency: The content of specific elements in the composite catalyst material in the mixed solution before and after separation is determined by atomic absorption spectrometry, thereby calculating the content of the composite catalyst material. The calculation formula is (content before separation - content after separation) / content before separation × 100%; Mineral extraction amount: The extracted minerals were weighed using an electronic balance in grams (g); Liquid fertilizer stability: Place the liquid fertilizer under the same conditions and let it stand for a week. Then use a measuring cylinder to measure the ratio of the sediment volume to the total volume to evaluate the stability. The smaller the sediment volume ratio, the higher the stability. It is divided into three levels: stable (sediment volume ratio is less than 5%), relatively stable (sediment volume ratio is 5%-10%), and unstable (sediment volume ratio is greater than 10%). Nutrient content of liquid fertilizer: Spectrophotometry is used to detect the content of the main nutrients nitrogen (N), phosphorus (P2O5), and potassium (K2O) in liquid fertilizer, and the unit is grams per liter (g / L).

[0031] Threonine decomposition efficiency: The threonine decomposition efficiency was calculated by detecting the residual threonine in the treated waste liquid by high performance liquid chromatography. The calculation formula was (initial threonine content - residual threonine content) / initial threonine content × 100%.

[0032] As attached Figure 2As shown, by comparing Example 1 with Comparative Examples 1, 2, and 3, the results clearly show that Example 1 has the best effect. In terms of the separation efficiency of the composite catalyst material, Example 1 is as high as 95.2%, which is much higher than other comparative examples. In terms of the amount of mineral extraction, Example 1 is 25.8 g, which is significantly more than the comparative example. In terms of liquid fertilizer stability, the precipitation volume of Example 1 accounts for only 3.2%, which is in a stable state, while the comparative example is relatively stable or unstable. In terms of nutrient content, the nitrogen, phosphorus, and potassium contents in Example 1 are also higher than those in the comparative example. The threonine decomposition efficiency of Example 1 reaches 98.5%. In summary, it can be seen from the experimental results that Example 1 is outstanding in terms of efficient separation of composite catalyst materials, efficient extraction of minerals, and preparation of stable and nutritious liquid fertilizers, and is indeed the best based on the three beneficial effects.

[0033] Although the present invention is disclosed as above in terms of preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, any modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for extracting minerals from threonine fermentation wastewater to prepare fertilizer, characterized in that: The method for preparing the fertilizer specifically comprises the following steps: Step 1: collecting threonine fermentation waste liquid and pre-treating it, allowing the threonine fermentation waste liquid to stand for a period of time by gravity sedimentation, then filtering it with a filter, then adding a flocculant, polyaluminium chloride, stirring evenly and allowing it to stand for a period of time again, to complete the preliminary filtration and purification of the waste liquid; Step 2: Decomposing threonine, firstly preparing a composite catalyst material, selecting a carbon nanotube material modified with graphene nanosheets, pre-treating it with dilute hydrochloric acid, then subjecting it to high-temperature carbonization treatment to obtain a porous carbon skeleton, and then immersing it in a manganese sulfate solution by an impregnation method to obtain a composite catalyst material, putting the prepared composite catalyst material into the pre-treated waste liquid, and adding a hydrogen peroxide solution with a concentration of 1.5 to carry out an oxidation reaction; Step 3: filtering the mixed solution after threonine decomposition by vacuum filtration to separate the composite catalyst material, and then further treating the filtrate by adjusting the pH value of the filtrate, and then adding sodium carbonate precipitant to the filtrate for precipitation for a period of time, and then filtering and collecting the precipitate, and collecting the obtained precipitate after washing and drying; Step 4, preparing a composite material consisting of modified diatomaceous earth and functionalized cellulose, first modifying the diatomaceous earth, first grinding the diatomaceous earth, then soaking it in a hydrochloric acid solution for a period of time, washing and drying it, and then soaking it in a solution containing a metal ion chelating agent for a period of time to obtain modified diatomaceous earth, then functionalizing the natural cellulose, soaking the natural cellulose material cotton fiber in a sodium hydroxide solution for a period of time to react, washing it with deionized water after the reaction is completed, adding an initiator ammonium persulfate to an acrylic acid solution containing a grafting monomer to react to obtain functionalized cellulose, mixing the modified diatomaceous earth and the functionalized cellulose to obtain a composite material, filtering the waste liquid again and then putting it into the composite material for reaction, filtering and separating the composite material after the reaction, and then soaking the composite material in a dilute hydrochloric acid solution for a period of time to obtain a solution rich in minerals; Step 5: Take the product after the decomposition of threonine in step 2 and the mineral-rich solution obtained in step 4, mix them evenly to obtain a mineral solution, dissolve the organic polymer polyacrylamide in water, and then add the mineral solution to the organic polymer solution for reaction. Then, add the plant growth regulator indoleacetic acid, potassium dihydrogen phosphate buffer and stabilizer disodium ethylenediaminetetraacetate to the mixed solution, then adjust the pH value of the solution and stir evenly to obtain liquid fertilizer.

2. The method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer according to claim 1, characterized in that: In the step 1, the standing time of the threonine fermentation waste liquid is 30 minutes, the filtration pore size of the filter is 0.5 mm-1.2 mm, and the amount of flocculant polyaluminium chloride added is 0.5%-1% of the volume of the waste liquid. After adding, it is stirred evenly and then stood for another hour.

3. The method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer according to claim 1, characterized in that: In the step 2, the pretreatment process of the carbon nanotube material modified with graphene nanosheets is as follows: the carbon nanotube material modified with graphene nanosheets is soaked in dilute hydrochloric acid for 2h-3h, then washed with deionized water until neutral, and then dried at 80℃-100℃ for 4h-6h. After the pretreatment, it is subjected to high-temperature carbonization treatment. The high-temperature carbonization treatment process is as follows: in the presence of inert gas nitrogen, the temperature is raised to 600℃-80℃ at a heating rate of 5℃ / min-10℃ / min. 0℃, high temperature carbonization treatment time is 3h-5h, and then activation treatment is carried out with activator carbon dioxide at 700℃-900℃ for 2h-4h, and then immersed in manganese sulfate solution by impregnation method. The impregnation process is as follows: the porous carbon skeleton is immersed in a manganese sulfate solution with a concentration of 0.5mol / L-1mol / L for 4h-6h, and then dried at 80℃-120℃ for 6h-8h, and then calcined at 300℃-400℃ for 2h-3h.

4. The method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer according to claim 1, characterized in that: In the step 2, the composite catalyst material is put into the pretreated waste liquid and then a hydrogen peroxide solution is added to carry out an oxidation reaction. The concentration of the hydrogen peroxide solution is 10%-20%, and the amount of the hydrogen peroxide solution added is 5%-10% of the volume of the waste liquid. The reaction is carried out for 2.5h-4.5h at a temperature of 45°C-55°C and a stirring speed of 120r / min-180r / min.

5. The method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer according to claim 1, characterized in that: In the step three, the mixed solution after threonine decomposition is filtered by vacuum filtration with a filter membrane pore size of 0.1mm-0.3mm and a vacuum degree of -0.05MPa to -0.08MPa. The filtrate is then treated by first adjusting the pH value to 6.5-7.5, and then adding sodium carbonate precipitant for a precipitation time of 2h-4h.

6. The method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer according to claim 1, characterized in that: In the step 4, the diatomite modification process is as follows: first grind the diatomite to a particle size of 0.1mm-0.5mm, soak it in a hydrochloric acid solution with a concentration of 0.5mol / L-1mol / L for 2h-3h, dry it at 100℃-120℃ for 3h-4h after washing, and then soak it in a metal ion chelating agent solution with a concentration of 0.2mol / L-0.5mol / L, and react it at 40℃-50℃ for 3h-4h. The natural cellulose functionalization treatment process is as follows: soak the natural cellulose material cotton fiber under alkaline conditions of 1mol / L-2mol / L sodium hydroxide solution for 2h-3h, add the initiator ammonium persulfate to the acrylic acid solution containing the grafting monomer after washing, and react it at 50℃-60℃ for 3h-4h to obtain functionalized cellulose.

7. The method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer according to claim 1, characterized in that: In the step 4, the modified diatomaceous earth and the functionalized cellulose are mixed in a mixing ratio of 1:1.5-2 by mass ratio of the modified diatomaceous earth to the functionalized cellulose, the waste liquid is reacted with the composite material again at 25°C-35°C for 2h-3h, the concentration of the dilute hydrochloric acid solution for soaking the composite material is 0.5mol / L-1mol / L, and the soaking time is 2h-3h.

8. The method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer according to claim 1, characterized in that: In the step 5, the organic polymer polyacrylamide is dissolved in water, specifically, 10mL-15m water is added per gram of polyacrylamide to form a solution with a concentration of 5%-10%, the mass ratio of the polyacrylamide solution and the mineral solution added to the organic solution is 1:3-4, and the reaction is controlled to stir and mix at 40°C-50°C for 2h-3h.

9. The method for extracting minerals from threonine fermentation waste liquid to prepare fertilizer according to claim 1, characterized in that: In the step 5, the concentration of indoleacetic acid, a plant growth regulator, added to the mixed solution is 0.01 mol / L-0.03 mol / L, potassium dihydrogen phosphate buffer is added until its concentration in the solution is 0.1 mol / L-0.3 mol / L, the amount of disodium ethylenediaminetetraacetate, a stabilizer, added is 0.5%-1% of the mass of the solution, and then the pH value of the solution is adjusted to 7-7.5, and finally stirred at a stirring speed of 60 r / min-100 r / min for 30 min-60 min to obtain a liquid fertilizer.